2023
DOI: 10.1186/s10195-023-00693-8
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and progression of osteoarthritis following curettage and cementation of giant cell tumor of bone around the knee: long-term follow-up

Abstract: Background Giant cell tumor of bone (GCTB) is a benign locally aggressive tumor frequently treated with intralesional curettage and cementation. The aim of this study was to investigate the long-term incidence of arthritic changes following curettage and cementation of GCTB around the knee. Materials and methods This study was a retrospective review of patients with GCTB around the knee treated with curettage and cementation with a minimum follow-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Rate of osteoarthrosis for patients undergoing surgery involving PMMA is estimated at 12 % in short term follow-up in initial studies describing cementing techniques. Other studies have shown degenerative changes in 26–33 % of patients, and one retrospective study with a minimum follow-up of 10 years reported a rate of 21 %, although only 8 % experienced progression of their arthritis during the follow-up period [ 74 , 76 , 95 , 96 ]. Some studies have shown that PMMA is an independent risk factor for total joint replacement [ 63 ].…”
Section: Secondary Osteoarthritismentioning
confidence: 99%
“…Rate of osteoarthrosis for patients undergoing surgery involving PMMA is estimated at 12 % in short term follow-up in initial studies describing cementing techniques. Other studies have shown degenerative changes in 26–33 % of patients, and one retrospective study with a minimum follow-up of 10 years reported a rate of 21 %, although only 8 % experienced progression of their arthritis during the follow-up period [ 74 , 76 , 95 , 96 ]. Some studies have shown that PMMA is an independent risk factor for total joint replacement [ 63 ].…”
Section: Secondary Osteoarthritismentioning
confidence: 99%
“…A group of authors from Burlington (Vermont, USA) attempted a decision tree analysis to address this question, looking at alternative solutions and expected outcomes. 1 The…”
Section: Foot and Anklementioning
confidence: 99%
“…This retrospective study based in ShebinEl-Kom (Egypt) sought to provide long-term insights into this issue 1. The investigation focused on determining the frequency of arthriticchanges occurring a decade or more after curettage and cementation of GCTs around the knee.…”
mentioning
confidence: 99%